The flow of hybrid nanofluid past a permeable shrinking sheet in a Darcy–Forchheimer porous medium with second-order velocity slip - Abu Bakar, Shahirah; Wahid, Nur Syahirah; Md Arifin, Norihan; Khashi’ie, Najiyah Safwa (Taylor and Francis, 2022)
The objective of this research is to study the significance of second-order velocity slip in a Darcy–Forchheimer porous medium with the hybrid nanofluid flow toward a permeable shrinking surface. Heat generation and radiative heat flux are introduced in the energy model. Two distinct nanoparticles of aluminum oxide (Al2O3) and copper (Cu) are used to represent the hybrid nanofluid flow with water (H2O) as the base fluid. An appropriate method of similarity transformation is applied to reduce a PDE system into a model of non-linear ODEs. With the aid of a bvp4c solver in Matlab, the respective findings are graphically presented for the profiles of velocity and temperature, skin friction coefficient, and Nusselt numbers with physical parameters, such as suction, porous medium permeability, Darcy–Forchheimer number, shrinking, radiation, and nanoparticle volume fraction. The hybrid nanofluid presented a higher estimation of heat and mass transfer rates than the classic mono-nanofluid. Moreover, the parameters of Darcy–Forchheimer number and second-order velocity slip significantly expand the fluid flow. It is found that the occurrence of opposing flow (λ < 0) will generate two solutions, where the implementation of stability analysis perceived the first solution to be the most realizable.